Pain in women - Chin, May L.; Fillingim, Roger B., 1962-; Ness, Timothy J. (New York : Oxford University Press, 2013)
This text addresses the current understanding of mechanisms related to sex differences, and the clinical management of common acute and chronic painful conditions in women, using up-to-date evidence-based information. The painful conditions discussed include those that are specific to female anatomy and physiology and conditions that have a higher female prevalence.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Pain; Pain -- Treatment; Women